Difference between revisions of "022 Exam 2 Sample B, Problem 7"

From Math Wiki
Jump to navigation Jump to search
 
(5 intermediate revisions by the same user not shown)
Line 16: Line 16:
 
|-
 
|-
 
|
 
|
::<math style="vertical-align: -70%;">\int x^n dx \,=\, \frac{x^{n + 1}}{n + 1}+C,</math>&thinsp; for <math style="vertical-align: -23%;">n\neq 0</math>.
+
::<math style="vertical-align: -70%;">\int x^n dx \,=\, \frac{x^{n + 1}}{n + 1}+C,</math>&thinsp; for <math style="vertical-align: -22%;">n\neq -1</math>,
 +
|-
 +
|as well as the convenient antiderivative:
 +
|-
 +
|
 +
::<math>\int e^x\,dx\,=\,e^x+C.</math>
 
|}
 
|}
  
Line 22: Line 27:
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
!Step 1: &nbsp;
+
!(a) Step 1: &nbsp;
|-
 
|(a) Use a ''u''-substitution with <math style="vertical-align: -8%">u = 3x^2 + 1.</math> This means <math style="vertical-align: 0%">du = 6x\,dx</math>, or <math style="vertical-align: -20%">dx=du/6</math>. After substitution we have
 
::<math>\int x e^{3x^2+1}\,dx = \frac{1}{6} \int e^{u}\, du. </math>
 
 
|-
 
|-
|(b) We need to use the power rule to find that <math>\int_2^5 4x - 5 \, dx = 2x^2 - 5x \Bigr|_2^5</math>
+
|(a) Use a ''u''-substitution with <math style="vertical-align: -8%">u = 3x^2 + 1.</math> This means <math style="vertical-align: 0%">du = 6x\,dx</math>, or <math style="vertical-align: -20%">dx=du/6</math>. Substituting, we have
 +
::<math>\int x e^{3x^2+1}\,dx \,=\,  \int xe^{u}\cdot\frac{du}{6}\,=\,\frac{1}{6}\int e^u\,du\,=\,\frac{1}{6}u. </math>
 
|}
 
|}
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
!Step 2: &nbsp;
+
!(a) Step 2: &nbsp;
 
|-
 
|-
|(a)
+
|Now, we need to substitute back into our original variable using our original substitution <math style="vertical-align: -5%">u = 3x^2 + 1</math>
::<math>\frac{1}{6} \int e^{u}\, du = \frac{1}{6}e^u.</math>
 
 
|-
 
|-
|(b) We just need to evaluate at the endpoints to finish the problem:
+
| to find&nbsp; <math style="vertical-align: -60%">\frac{1}{6}e^u = \frac{e^{3x^2 + 1}}{6}.</math>
<math>\begin{array}{rcl}2x^2 - 5x \Bigr|_2^5 & = & 2(5^2) - 5(5) -(2(2)^2 - 5(2)\\
 
& = & 50 - 25 -(8 - 10)\\
 
& = & 25 +2\\
 
& = & 27
 
\end{array}</math>
 
 
|}
 
|}
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
!Step 3: &nbsp;
+
!(a) Step 3: &nbsp;
|-
 
|(a) Now we need to substitute back into our original variables using our original substitution <math style="vertical-align: -5%">u = 3x^2 + 1</math>
 
 
|-
 
|-
| to find&nbsp; <math>\frac{1}{6}e^u = \frac{e^{3x^2 + 1}}{6}.</math>
+
|Since this integral is an indefinite integral, we have to remember to add a constant&thinsp; <math style="vertical-align: 0%">C</math> at the end.
 
|}
 
|}
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
!Step 4: &nbsp;
+
!(b): &nbsp;
 +
|-
 +
|Unlike part (a), this requires no substitution.  We can integrate term-by-term to find
 +
|-
 +
|
 +
::<math>\int_2^5 4x - 5 \, dx = 2x^2 - 5x \Bigr|_{x\,=\,2}^5.</math>
 +
|-
 +
|Then, we evaluate:
 
|-
 
|-
|Since this integral is an indefinite integral we have to remember to add a constant&thinsp; <math style="vertical-align: 0%">C</math> at the end.
+
|
 +
::<math>\begin{array}{rcl}2x^2 - 5x \Bigr|_{x\,=\,2}^5 & = & 2(5^2) - 5(5) -(2(2)^2 - 5(2))\\
 +
& = & 50 - 25 -(8 - 10)\\
 +
& = & 25 +2\\
 +
& = & 27.
 +
\end{array}</math>
 
|}
 
|}
  
Line 61: Line 68:
 
!Final Answer: &nbsp;
 
!Final Answer: &nbsp;
 
|-
 
|-
|(a)
+
|'''(a)'''
::<math>\frac{e^{3x^2 + 1}}{6} + C.</math>
+
::<math>\int xe^{3x^2+1}\,dx\,=\,\frac{e^{3x^2 + 1}}{6} + C.</math>
 +
|-
 +
|'''(b)'''
 
|-
 
|-
|(b) <math>27</math>
+
|
 +
::<math>\int_2^54x - 5\,dx\,=\,27.</math>
 
|}
 
|}
  
[[022_Exam_2_Sample_A|'''<u>Return to Sample Exam</u>''']]
+
[[022_Exam_2_Sample_B|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 16:28, 17 May 2015

Find the antiderivatives:

(a)


(b)
Foundations:  
This problem requires Integration by substitution (u - sub): If   is a differentiable functions whose range is in the domain of , then
We also need our power rule for integration:
  for ,
as well as the convenient antiderivative:

 Solution:

(a) Step 1:  
(a) Use a u-substitution with This means , or . Substituting, we have
(a) Step 2:  
Now, we need to substitute back into our original variable using our original substitution
to find 
(a) Step 3:  
Since this integral is an indefinite integral, we have to remember to add a constant  at the end.
(b):  
Unlike part (a), this requires no substitution. We can integrate term-by-term to find
Then, we evaluate:
Final Answer:  
(a)
(b)

Return to Sample Exam